Smokers' unprompted comments on cigarette additives during conversations about the genetic basis for nicotine addiction: a focus group study - Sydney E. Philpott; Sarah Gehlert; Erika A. Waters (BMC, 2018)
Abstract Background Research designed to elicit smokers' cognitive and affective reactions to information about chemicals that tobacco companies add to cigarettes ("additives") found that knowledge is limited. However, little is known about smokers' unprompted thoughts and feelings about additives. Such information could be used to shape future communication efforts. We explored the content and possible functions of spontaneous statements about cigarette additives made by smokers during a study examining reactions to learning about the genetic link to nicotine addiction. Methods Adult smokers (N = 84) were recruited from a medium-sized Midwestern city. Focus groups (N = 13) were conducted between April-September 2012. Data were analyzed by 2 coders using thematic analysis. Results Comments about cigarette additives arose without prompting by the focus group moderator. Three main themes were identified: (1) discussing additives helped participants navigate the conceptual link between smoking and genetics, (2) additives were discussed as an alternative mechanism for addiction to cigarettes, and (3) additives provided an alternative mechanism by which cigarette smoking exacerbates physical harm. Notably, discussion of additives contained a pervasive tone of mistrust illustrated by words like "they" and "them," by statements of uncertainty such as "you don't know what they're putting into cigarettes," and by negative affective verbalizations such as "nasty" and "disgusting". Conclusions Participants had distinct beliefs about cigarette additives, each of which seemed to serve a purpose. Although mistrust may complicate communication about the health risks of tobacco use, health communication experts could use smokers' existing beliefs and feelings to better design more effective anti-smoking messages.